The fitness costs of reproductive specialization scale inversely with organismal size - Christopher Zhang; Eric Libby; Anthony Burnetti; Matthew D. Herron; William C. Ratcliff (Proceedings of the National Academy of Sciences, 2026)
The evolution of reproductive specialization, in which somatic cells forfeit reproduction, represents a fundamental innovation in complex multicellular life. This specialization imposes a fitness cost: because somatic cells do not produce offspring, organisms that invest in soma have reduced fecundity. The magnitude of this cost might be expected to depend simply on the proportion of cells allocated to soma. Here, we show that these costs also decrease with the logarithm of organism size, because larger organisms require proportionally more cell divisions for development, diluting the rate at which reproductive costs compound across multicellular generations. We derive this result analytically and validate it with data from the volvocine green algae. When somatic cells provide a compensating survival benefit, a positive feedback emerges: larger organisms can afford greater somatic investment, which in turn favors further size increases. This size-scaling relationship helps explain the broad association between large organism size and multicellular complexity.